Gamifying fake news: Engaging youth in the participatory design of news literacy games. (June 2020) - Literat, Ioana; Chang, Yoo Kyung; Hsu, Shu-Yi
This article discusses the potential of participatory game design to encourage and capture youth reflection, discussion, and participation around news literacy topics. Based on data obtained during a game design workshop with youth participants, we analyze two youth-produced games about fake news and discuss the personal, social, and cultural dimensions of youth attitudes and practices in relation to news literacy, as manifested through the process of game design. Our findings paint a rich picture of the ways in which youth understand and engage with fake news, their attitudes toward news literacy, and their playful approaches to collaboratively designing and prototyping news literacy games. This research sheds light on the opportunities and challenges related to the use of games and participatory game design for news literacy research and education, while also contributing to our understanding of the emerging processes that can support youth's roles as designers, and not only consumers, of educational games about the news.